2015
DOI: 10.1049/iet-its.2013.0136
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intelligent speed adaptation technology on older drivers’ driving performance

Abstract: Excess speeding on roads with a low-speed limit is a key error in drivers of all ages although the reasons for speeding can be significantly different. Drivers aged over 60 are generally more cautious, and take fewer risks than younger aged drivers. This study investigates whether Intelligent Speed Adaptation (ISA) technology can assist older drivers in maintaining vehicle speed. The technology can be employed in three ways: advisory (AISA), differential (DISA) and mandatory (MISA). Twentysix drivers aged over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 12 publications
1
25
0
Order By: Relevance
“…This could possibly be explained by the previous finding that older people's already slower reaction time involved a "protective" mechanism which prevented that from slowing down even further in the more difficult tasks; the price of maintaining reaction time is reduced accuracy [37]. In general, this finding corresponds with those of previous studies which suggest that older drivers interact with technologies differently compared to younger drivers, and their needs should be carefully considered in the design of new technologies [21,38].…”
Section: Discussionsupporting
confidence: 80%
“…This could possibly be explained by the previous finding that older people's already slower reaction time involved a "protective" mechanism which prevented that from slowing down even further in the more difficult tasks; the price of maintaining reaction time is reduced accuracy [37]. In general, this finding corresponds with those of previous studies which suggest that older drivers interact with technologies differently compared to younger drivers, and their needs should be carefully considered in the design of new technologies [21,38].…”
Section: Discussionsupporting
confidence: 80%
“…Similarly, Weihong, Blythe, Edwards, Pavkova, and Brennan (2015) found that 80% of 60+ drivers did not control their speed appropriately in free-flow traffic conditions and older drivers have been found to commit more driving errors when compared to younger drivers, however their speed adjustment and lane position was improved in automatic transmission cars (Selander, Falkmer, & Bolin, 2012). Furthermore, older drivers usually experience high crash risk comparing to other cohorts in urban environments, due to their inappropriate speed control performance (Weihong et al, 2015). Hence, the mean speed and standard deviation of speed can indicate the drivers' speed control performance (Reed & Green, 1999).…”
Section: Speed Controlmentioning
confidence: 98%
“…It is known that older and novice drivers are more likely to respond inappropriately to road geometries and traffic signs, which require them to control driving speed (Chan, Pradhan, Pollatsek, Knodler, & Fisher, 2010). Similarly, Weihong, Blythe, Edwards, Pavkova, and Brennan (2015) found that 80% of 60+ drivers did not control their speed appropriately in free-flow traffic conditions and older drivers have been found to commit more driving errors when compared to younger drivers, however their speed adjustment and lane position was improved in automatic transmission cars (Selander, Falkmer, & Bolin, 2012). Furthermore, older drivers usually experience high crash risk comparing to other cohorts in urban environments, due to their inappropriate speed control performance (Weihong et al, 2015).…”
Section: Speed Controlmentioning
confidence: 99%
“…To reduce traffic accidents caused by elderly drivers, which is currently a major problem in Japan (1) , more advanced safety technologies that can assist such drivers are required (2)(3)(4) (5) . Because both physical and cognitive abilities of elderly drivers decline due to their aging, advanced driving assistance systems in the intelligent vehicle with a certain level of autonomy seems desirable.…”
Section: Introductionmentioning
confidence: 99%